Evaluation of Twenty Chemical Elements in Thyroid with Hashimoto’s thyroiditis using X-Ray Fluorescent and Neutron Activation Analysis - Zaichick, Vladimir (Jour Med Resh and Health Sci, 2021)
Background: Hashimoto’s thyroiditis (HT) is an internationally important health problem. Objectives: Role of chemical elements (ChE) in etiology and pathogenesis of HT is unclear. The aim of this exploratory study was to assess whether there were significant changes in thyroid tissue levels of twenty ChE (Ag, Br, Ca, Cl, Co, Cr, Cu, Fe, Hg, I, K, Mg, Mn, Na, Rb, Sb, Sc, Se, Sr, and Zn) are present in the HT transformed thyroid. Methods Twenty ChE of thyroid tissue were determined in 8 patients with HT. The control group included thyroid tissue samples from 105 healthy individuals. Measurements were conducted using combination of non-destructive methods such as energy dispersive X-ray fluorescent analysis and instrumental neutron activation analysis. Results Reduced mean values of Ca and I content almost in two times, while elevated level of Ag, Cu, Hg, and Na in 21, 1.2, 30, and 1.5 times, respectively, were found in thyroid with HT in comparison with normal level. Conclusions There are considerable changes in some ChE contents in tissue of thyroid with HT. Thus, it is reasonable to assume that the levels of these ChE in affected thyroid tissue can be used as HT markers. However, this topic needs additional studies.